Darn Acemoglu and James A. Robinson. Why Nations Fail: The Origins of Power, Prosperity, and Poverty. New York: Crown Business. 2012. 529 pages. U.S $ 17.00. (The Pakistan Development Review, 2012)
“Why Nations Fail: The Origins of Power, Prosperity and Poverty” is an impressive book by Daron Acemoglu and James A. Robinson. In this book, the authors attempt to solve the longstanding puzzle that why some nations, such as the United Sates, Great Britain, Germany, etc. are rich today, and why the others, such as Zimbabwe, Ghana, Egypt, etc. are poor. The authors show with the help of substantial historical evidence that man-made economic and political institutions matter for the vast differences in the level of economic development among countries. They argue history is the key to understand the difference and evolution of economic and political institutions in different parts of the world. During historical evolution of the institutions, small differences and contingency (e.g., Black Death) matter a lot. According to them, it is not the geography, culture, weather or the choice of wrong policies that make countries rich or poor but it is the institutions that make countries rich or poor.